Sweden and the Transformation of Northern Historiography - Knoespel, Kenneth J. (Journal of Northern Studies, 2014)
Viewed from the Mediterranean South, the North was associated from the earliest ages with a darkness linked with strange languages, distance, alien cultural behavior, and just plain bad weather. This darkness—or the fog and mist if we use the early description of Marco Polo—was not ignored but itself became a screen upon which the South could project an ever-growing list of fantasies. While Swedish figures such as Olof Rudbeck made elaborate national projections about the role of the North in civilization, Carl von Linné and others succeeded in translating fantasies of political empire into kingdoms of knowledge. Drawing on Swedish historiography and the history of technology, this essay poses questions about the ways Sweden’s often invisible presence continues to shape the formulation of knowledge.